A C0-continuous RZT beam element for the damped response of laminated structures. (1st November 2015) - Treviso, A.; Mundo, D.; Tournour, M.
Abstract: Composite and sandwich structures are appealing to many engineering fields. Despite the increased rate of application, their cost remains higher compared to traditional engineering materials. One of the reasons is the necessary use of experimental characterization and validation of materials and structures respectively. One way to reduce costs is to increase predictive capabilities of simulation software. With this respect, finite element analysis is a powerful tool. However, the finite element modelling of composites and sandwich structures requires dedicated strategies in order to account for their non-homogeneity and anisotropy. This paper presents a C 0 -continuous beam element based on the RZT which is employed to predict the dynamic response of composite and sandwich structures. In particular, structures with viscoelastic layers for vibrations reduction will be considered. The damping modelling will also be addressed. The main objective is to assess the capabilities of the RZT for both dynamic response and damping predictions of laminates and sandwiches.